(untitled) (Revista Educação, Artes e Inclusão, 2020)
This article intends to problematize the idea of ​​small displacements that are experienced in the context of training practices that seek to compose other ways of thinking and acting in health, as a possibility to promote access to aesthetic experience and life in its expressive and creative power. To this end, we will present some aspects of a creation and education project that involves women from a vulnerable region of Santos, who present different physical, emotional and social challenges, and students from a public university. In this project, different proposals were made mobilized by the arts in their multiple languages, in order to promote sensitive and playful experiences that can produce small displacements. quicken bodies, activate memories, imaginations, recognize and awaken desires, affect and be affected by the encounter between bodies. We consider small displacements as minor movements within experiences, which have the power to activate and affect processes of subjectivation and the production of other sensitivities. We experimented dancing, singing, playing, dramatizing, moving and pausing, talking and silencing, among other things, attentive to what is small, the microscopic marks, to the details of events. Anchored in a micropolitical perspective, we bet on small interferences as a way of producing inventive training for students and the increase of individual and collective power with all and all participants of this collaborative project that takes place at the interface of body, art, health and education.